HUBUNGAN ANTARA KARAKTERISTIK IBU HAMIL DENGAN KEJADIAN ANEMIA DI RUMAH SAKIT UMUM DAERAH Dr.SAYIDIMAN MAGETAN - Kusuma, Wanda Pradina; , Faizah Betty Rahayuningsih, S.Kep., M.Kes; , Sulastri, SKp., M.Kes (2011)
Prevalence rate of anemia in pregnant women is increasing in Indonesia. Most of the causes of anemia in Indonesia is deficiency iron in the need for produce the hemoglobin. Less iron anemia suffered by many pregnant women, nursing mothers, and women of childbearing age because of the need for iron during pregnancy was higher than pre-pregnancy iron requirement. Incidence rate comsumption of anemia in pregnant women are indirectly influenced by the characteristics contained in each of the pregnant women. Characteristics of mother are one aspect in determining the status of anemia in pregnant women. Pregnancy with anemia, and malnutrition in pregnant women are the main cause of maternal deaths are extremely complex. The purpose of this study was to determine the relationship between characteristics of pregnant women in this regard is the maternal age, pregnancy interval, level of education and parity with the incidence of anemia at the General Hospital of Dr.Sayidiman Magetan. The study was a descriptive correlative study using cross sectional design. The research sample of 70 pregnant women who examined its contents in poly obstetrics and gynecology Dr Regional General Hospital. Sayidiman Magetan with sample selection using total sampling technique. The collecting data using medical record data and check list. Processing data using Chi Square analysis techniques. The results showed that maternal age of majority at the age of 20-35 years (52.9%), pregnancy interval < 2 years (52.9%), level of maternal education < 9 years (51.4%), and maternal parity > 6 times (54.3%). The results showed that there are relationships between maternal age (p value = 0.006), and spacing of pregnancy (p value = 0.017) and anemia in pregnant women. There is no relationship between education level (p value = 0.089), and parity (p value = 0.107) and anemia in pregnant women.